Low-Dimensional Functional Materials - Egger, Reinhold.; Egger, Reinhold.; Matrasulov, Davron.; Matrasulov, Davron.; Rakhimov, Khamdam.; Rakhimov, Khamdam. (NATO Science for Peace and Security Series B: Physics and Biophysics,, 2013)
Maintaining and improving energy security is one of the biggest challenges worldwide.  The NATO ARW conference in Tashkent, October 2012, was devoted to discussing visions and concepts that are currently discussed in different research fields. Leading scientists have written concise contributions to introduce the reader to this exciting topic.  The present volume summarizes the discussions at the conference.